(untitled) (Journal of Atomic and Molecular Sciences, 2012)
The nucleation of graphene on Ni surface, as well as on the step, is studied using a tight binding method of SCC-DFTB. The result demonstrates that the fcc configuration has the lowest total energy and thus is the most stable one compared to the other two structures when benzene ring is absorbed on the Ni(111) surface. The activity of marginal growth graphene's carbon atoms decreases from the boundary to the center, when they are absorbed on the substrate. Graphene layer can grow continuously on step surface formed by intersection of Ni(111) and Ni(111) surface. Meanwhile, a mismatch will occur between the graphene layer and Ni surface and thus leads to flaws when the layer grows larger. Reducing the mismatch between the graphene and the step surface will benefit the growth of graphene of large area and high quality.